Implementation of Child Protection Policy in a Public School - Japhet Z. Matulac; Karen L. Zamora (Philippine Social Science Journal, 2020)
Child protection policy gives guidelines and rules to the Child Protection Committee to create a secured and safe environment for learners. It is a tool that protects both learners and school personnel by clearly characterizing the arrangements and measures for child protection and by practicing a reliable behavior toward child-safety. Hence, the paper examines the level of implementation of the Department of Education (DepEd) Child Protection from a public school in the Division of Bacolod City during the School Year 2018-2019. This study was conducted to create awareness among school personnel regarding the strengths and weaknesses of the implementation of the Child Protection Policy in its jurisdiction.  The researcher utilized the result of the study in making an action plan that serves as a mechanism to ensure the school's full implementation of its Child Protection Policy.